GENOTYPE AND TIME OF INOCULATION EFFECTS ON DON PER GRAIN AND GRAIN WEIGHT OF WINTER WHEAT UNDER TWO ENVIRONMENTAL CONDITIONS - Okereke, Victor Chijioke (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Experiment was conducted using near isogenic lines of Mercia background in a controlled environment to evaluate the mean effect of timing of inoculation and subsequent increase in temperature on deoxynivalenol (DON) concentration, amount of DON per grain and grain weight. The experiment was completely randomised consisting of three genotypes differing in semi-dwarfing alleles; Mercia 0 Rht-B1a + Rht-D1a (wild type), Mercia 1 (Rht-B1b) and Mercia 2 (Rht-D1b) and four inoculation timings. The experiment was a complete factorial combination with four randomised replicates. Data showed that genotype differed in DON concentration (P<0.001), DON per grain (P=0.006) and mean grain weight (P=0.001) while time of inoculation influenced mean grain weight (P<0.001) and DON Concentration (P<0.001) but not Don per grain (P=0.23). Temperature influenced mean grain weight (P=0.002) with high temperature adversely affecting the size of the wheat grains.